Deoxynivalenol downregulates NRF2-induced cytoprotective response in human hepatocellular carcinoma (HepG2) cells. (15th April 2021) - Ndlovu, Siqiniseko; Nagiah, Savania; Abdul, Naeem Sheik; Ghazi, Terisha; Chuturgoon, Anil A.
Abstract: Deoxynivalenol (DON) commonly infects agricultural foods; it exhibits toxicity by inducing oxidative stress and inhibiting protein synthesis. Nuclear factor erythroid 2-related factor 2 (NRF2) regulates the cellular antioxidant response. We investigated the cytotoxicity of DON and its effect on the NRF2 antioxidant response in HepG2 cells. The Methyl Thiazol Tetrazolium (MTT), glutathione (GSH) and ATP assays evaluated toxicity, whilst lipid peroxidation and membrane damage were assessed using the Thiobarbituric acid reactive substance (TBARS) and lactate dehydrogenase (LDH) assays. Protein expression of NRF2, phosphorylated (p-ser40) NRF2, catalase (CAT), superoxide dismutase 2 (SOD2), and Sirtuin 3 (Sirt3) were quantified by Western Blotting. Gene expression of glutathione peroxidase ( GPx ), CAT and SOD2 was determined using qPCR. DON decreased cell viability, GSH concentrations and ATP levels and increased lipid peroxidation and membrane damage. DON significantly decreased total NRF2 and increased p-NRF2 and downregulated the transcription and translation of NRF2 target antioxidant enzymes. Further, expression of the mitochondrial stress response protein, Sirt3 was significantly decreased. In conclusion, DON induced oxidative stress and downregulated NRF2-induced cytoprotection by suppressing the antioxidant signalling mechanism in HepG2 cells. Graphical abstract: Image 1 Highlights: Deoxynivalenol (DON) induced oxidative stress in HepG2 liver cells. DON decreased cell viability, glutathione (GSH) and ATP concentrations. DON significantly decreased total Nuclear factor erythroid 2-related factor 2 (NRF2) and increased p-NRF2 . DON downregulated the transcription and translation of NRF2 target antioxidant enzymes. DON significantly decreased Sirtuin 3 (Sirt3) expression.